Determinants Related to the Performance of Inpatient Nurses at Permata Cibubur Hospital - Henrika Retno K.M; Yuli Prapanca Satar; Purwanti Aminingsih; Mira Roziati Dachlan; Titik Widayati (Journal of Ageing And Family, 2024)
In improving the quality of hospital health services, one important role is to focus on the quality of human resources, namely nursing services. The contribution of nursing services is assessed in the performance of nurses. There are several factors that can affect worker performance, such as motivation, work environment and the ability of the worker. This reseacrh aims to determine the determinant factors that are related to the performance of inpatient nurses at Permata Cibubur Hospital. Research Method: This research uses a quantitative with a cross-sectional design. The analysis in this study was used to determine the effect of each variable on the performance of inpatient nurses at Permata Cibubur Hospital. The number of samples needed in this study is 58 samples. Data analysis in this study uses logistic regression analysis Research Results: The results of the analysis show that nurses with good abilities have a tendency for good performance of 4.922 times higher than nurses with poor performance after being controlled by motivation and work environment variables. Then nurses with good motivation have a tendency for good performance of 4.269 times higher than nurses with poor performance after being controlled by nurse abilities and nurse environment. The most dominant nurse ability factor is related to nurse performance because it has the highest risk. Ability and motivation have an influence on improving the performance of inpatient nurses. Inadequate levels of work ability have a higher risk of having a negative impact on work. Worker motivation needs to be improved to prevent a decline in nurse performance.